Local Wisdom, Aesthetic Transformations, and Creative Pedagogy: A Qualitative Synthesis of Indonesian Performing Arts as Cultural–Educational Ecosystems - Putranto, Muhammad Fajar; Sukoco, Antonius; Suryadmaja, Galih (Gema Cendekia Institute, 2025)
This study synthesises interdisciplinary perspectives to examine how Indonesian performing arts function as dynamic cultural–educational ecosystems shaped by aesthetic expression, local wisdom, and creative pedagogical practices. Performing arts serve not only as artistic media but also as cultural spaces where identity, morality, symbolism, and social values are transmitted across generations. Local wisdom embedded in traditional arts strengthens their role in character formation and contextual learning, while contemporary forces such as modernisation, digitalisation, and global cultural flows increasingly influence how these traditions adapt and transform. Using a qualitative thematic-synthesis approach, the study reviews concepts from aesthetics, ethnography, cultural pedagogy, creative studies, and ethnomathematics to map the interconnected functions of performing arts. Four major thematic patterns emerge: aesthetic systems that evolve through symbolic structures and hybrid forms; the presence of moral, spiritual, and communal values; creative processes that mediate innovation while maintaining cultural continuity; and pedagogical potentials that support character development, cultural literacy, and creative reasoning. Overall, the study highlights Indonesian performing arts as an integrated ecosystem that bridges cultural transmission, creativity, and educational transformation. This synthesis provides a conceptual foundation for advancing future research and informing cultural and educational policy aimed at strengthening the sustainability and relevance of traditional performing-arts practices in contemporary contexts.